Propagation of plane waves in a rotating transversely isotropic two temperature generalized thermoelastic solid half-space with voids - Bijarnia, Rupender; Singh, Baljeet (Zielona Góra: Uniwersytet Zielonogórski)
The paper is concerned with the propagation of plane waves in a transversely isotropic two temperature generalized thermoelastic solid half-space with voids and rotation. The governing equations are modified in the context of Lord and Shulman theory of generalized thermoelasticity and solved to show the existence of four plane waves in the x - z plane. Reflection of these plane waves from thermally insulated stress free surface is also studied to obtain a system of four non-homogeneous equations
Keywords: anisotropy; generalized thermoelasticity; voids; plane waves; reflection; reflection coefficients